Educational Values in Islam and Confucianism: A Comparative Analysis - يوسف علي أحمد صالح النهدي; يَاجُوَانْ لِي (الآداب للدراسات اللغوية والأدبية)
This study compares the educational values rooted in Islamic and Confucian traditions, aiming to identify parallels that shape educational practices within these profound cultural and religious contexts. The methodology involves textual analysis and contextual evaluations, with primary references drawn from Islamic sources (the Holy Quran and Hadith) and Confucian texts (Analects, Mencius, Great Learning). It examines the comparative textual content and identifies core values, teachings, and morals defined by Islamic and Confucian principles. The findings reveal that both traditions emphasize moral and ethical development, disciplined learning, and the essential role of education in fostering societal harmony and effective governance. However, they differ in their emphasis, the roles of teacher, and the interplay between religious and secular knowledge. This comparative analysis highlights how foundational philosophical and spiritual texts influence educational paradigms and inform contemporary educational practices in societies shaped by Islam and Confucianism. The study underlines the moral and spiritual grounding of both values systems, particularly within multicultural and multi-religious contexts.